2021
DOI: 10.1111/dth.14999
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO 2 laser to improve noticeable scars after skin cancer surgery: An appraisal by the patients, laypersons, and experts

Abstract: Ablative fractionated carbon dioxide (fCO 2 ) laser may be a useful tool to improve noticeable scars after skin cancer surgery. Therefore we evaluated 40 patients who have been treated with fCO 2 laser for facial scars after skin cancer surgery. This retrospective study is based on blinded evaluation of pre-and postoperative photographs. Patients (n = 40), laypersons (n = 5) and experts (n = 5) evaluated the esthetics and the Vancouver scar scale as primary endpoints. Secondary endpoints included patient satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…A related study using CO 2 fractional laser to control scar growth after skin cancer surgery found that the CO 2 fractional laser was effective in controlling scar thickness and flexibility. 15 Furthermore, studies have shown that the use of tension-reducing devices such as tension-reducing tape 16 and tension reducers 17 , 18 are also clinically effective in inhibiting postoperative scar growth. These devices not only reduce the thickness of the scar, but also the width of the scar.…”
Section: Discussionmentioning
confidence: 99%
“…A related study using CO 2 fractional laser to control scar growth after skin cancer surgery found that the CO 2 fractional laser was effective in controlling scar thickness and flexibility. 15 Furthermore, studies have shown that the use of tension-reducing devices such as tension-reducing tape 16 and tension reducers 17 , 18 are also clinically effective in inhibiting postoperative scar growth. These devices not only reduce the thickness of the scar, but also the width of the scar.…”
Section: Discussionmentioning
confidence: 99%